Local laser fluence estimation in optical resolution optoacoustic angiography employing calibrated ultrasound detector - Daria Voitovich; Alexey Kurnikov; Anna Orlova; Aleksej Petushkov; Liubov Shimolina; Anastasia Komarova; Marina Shirmanova; Yu-Hang Liu; Daniel Razansky; Pavel Subochev (Photoacoustics, 2025)
Optical-resolution optoacoustic (photoacoustic) microscopy is a hybrid imaging modality combining focused optical excitation with ultrasound detection, thus achieving micrometer-scale spatial resolution and high-contrast angiographic imaging. Despite these important advantages, maintaining safe laser fluence levels is essential to prevent tissue damage while ensuring sufficient detection sensitivity. Here, we introduce a model that directly relates the detector’s noise-equivalent pressure (NEP) to the local laser fluence at the imaged blood vessel. The model incorporates acoustic propagation effects from an optoacoustic source to a spherically focused detector with limited aperture and bandwidth, offering a more comprehensive understanding of how fluence and ultrasonic sensitivity are interconnected. The effects of ultrasound generation propagation and detection were accounted for using analytical estimations and numerical simulations, while detector's NEP was experimentally measured with a calibrated hydrophone. The proposed model for evaluating of local laser fluence with a calibrated ultrasound detector was validated through in vitro experiments with superficially located blood layer and numerical Monte Carlo/k-Wave simulations featuring deeper vessels. In vivo experiments employing 532 nm laser excitation and wideband 1–30 MHz ultrasonic detection further demonstrated the model’s capacity for real-time adjustments of laser parameters to ensure tissue safety.